Chapter 4.7 Key Perspectives for a Long-term Career – Statistical Analysis of International Data for a New Profession - Shin Ito; Makiko Takahashi (Emerald Publishing Limited, 2023)
Research managers and administrators (RMAs) face the invisibility arising from the diversified work and ambiguous boundaries. Some reports pointed out the stress of RMAs. Moreover a long-term career is a critical matter for RMAs to succeed. Thus, this chapter aims to identify the relationship between the long-term career of RMAs and relevant factors. The dataset from Research Administration as a Profession 2 (RAAAP-2) allowed regression analysis considering national and regional differences in the analysis. The analysis included 3,235 respondents. The results indicated that job attraction perceived by RMAs and additional acquisition of academic degrees after engagement were positively and significantly related to the total years of experience. Moreover, the linear mixed models showed that country/regional variation and the total years of experience had a significant link even after controlling the other variables. The findings would highlight the attraction of research management and administration as a profession.
10.1108/978-1-80382-701-820231032; 10.1108/978-1-80382-701-820231032; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262